2020
DOI: 10.2147/hmer.s266841
|View full text |Cite
|
Sign up to set email alerts
|

<p>In Vitro Intraductal MRI and T2 Mapping of Cholangiocarcinoma Using Catheter Coils</p>

Abstract: Aim Diagnostic imaging of early-stage cholangiocarcinoma is challenging. A previous in vitro study of fixed-tissue liver resection specimens investigated T2 mapping as a method of exploiting the locally increased signal-to-noise ratio (SNR) of duodenoscope coils for improved quantitative magnetic resonance imaging (MRI), despite their non-uniform sensitivity. This work applies similar methods to unfixed liver specimens using catheter-based receivers. Methods Ex vivo int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is hoped that after validation is completed, the KKU staging system will employed in clinical staging and for pre-operative detection of pre-invasive neoplasms of the bile ducts in conjunction with radiological studies. 46,47 In 2017, Luvira V. and Eurboonyanun K (co-authors in our study) investigated intraductal papillary neoplasms of the bile duct (IPNB) with survival correlation of CCA patients via radio-pathological staging. Their study showed that IPNB correlated with early stage and predicted survival very well 48,49 In the future, this study will be modified for incorporation into the KKU staging system in guiding planning of surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that after validation is completed, the KKU staging system will employed in clinical staging and for pre-operative detection of pre-invasive neoplasms of the bile ducts in conjunction with radiological studies. 46,47 In 2017, Luvira V. and Eurboonyanun K (co-authors in our study) investigated intraductal papillary neoplasms of the bile duct (IPNB) with survival correlation of CCA patients via radio-pathological staging. Their study showed that IPNB correlated with early stage and predicted survival very well 48,49 In the future, this study will be modified for incorporation into the KKU staging system in guiding planning of surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Parametric mapping of liver disease has already been demonstrated with external coils ( 19 , 20 ), and we have previously reported methodology for intraductal MRI. Work has focused on duodenoscope modification for MR environments ( 21 ), the production of catheter-based receivers ( 22 ), the verification of the local SNR advantage of catheter receivers over torso array coils ( 23 ) and initial ex vivo imaging studies of surgical specimens ( 24 ).…”
Section: The Approaches To the Problemmentioning
confidence: 99%
“…Technical challenges included developing the design concept, simulating electro-magnetic performance, integrating flexible circuits on catheters, connecting receivers to auxiliary coil interfaces, and performing initial assessments of RF heating potential. Imaging has been carried out using a clinically available whole-body 3T Philips Achieva™ (Philips, Best, the Netherlands) MRI system in Khon Kaen in North-East Thailand, the epicenter of liver fluke-associated cholangiocarcinoma ( 24 ). Clinical challenges included synchronizing imaging with surgery in a busy hospital, identifying specimens suitable for cannulation, and correlating T2 maps of CCA with histopathology for the first time.…”
Section: The Approaches To the Problemmentioning
confidence: 99%
See 2 more Smart Citations